1983
DOI: 10.2105/ajph.73.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and tracing a population at risk: the DESAD Project experience.

Abstract: In recent years, medical record review has been used to alert patients who have received drugs or treatments that have newly discovered sideeffects. The experience of the national cooperative Diethylstilbestrol-Adenosis (DESAD) Project in identifying and notifying women exposed in utero to diethylstilbestrol (DES) shows this to be a difficult task. In order to identify 4,830 exposed women, 221,245 charts were reviewed. Detailed tracing data for one of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…100 DES was used in medicine and agriculture, beginning in 1947 and 1950, respectively, and continuing through 1971 when the FDA encouraged the discontinuation of its use because of its association with vaginal and cervical cancer. 102 , 103 , 104 , 105 This usage corresponds with the increase in the incidence of anorexia nervosa in 14–20 year old females, but not other age groups, in the US and Switzerland beginning about 1965 and continuing through 1976. 106 , 107 In addition, women exposed to DES when fetuses are 5 times more likely to show inexplicable weight loss and to be diagnosed with an eating disorder such as anorexia nervosa or bulimia nervosa, compared to women who were not exposed to the drug.…”
Section: Anorexia Nervosa and Ctamentioning
confidence: 82%
“…100 DES was used in medicine and agriculture, beginning in 1947 and 1950, respectively, and continuing through 1971 when the FDA encouraged the discontinuation of its use because of its association with vaginal and cervical cancer. 102 , 103 , 104 , 105 This usage corresponds with the increase in the incidence of anorexia nervosa in 14–20 year old females, but not other age groups, in the US and Switzerland beginning about 1965 and continuing through 1976. 106 , 107 In addition, women exposed to DES when fetuses are 5 times more likely to show inexplicable weight loss and to be diagnosed with an eating disorder such as anorexia nervosa or bulimia nervosa, compared to women who were not exposed to the drug.…”
Section: Anorexia Nervosa and Ctamentioning
confidence: 82%
“…Once again, this experience had many parallels with the experience and strategies used in the Diethylstilbestrol-Adenosis (DESAD) project conducted by Nash and colleagues [44]. The Tall Girls Study traced 87% of women identified as eligible from medical records [1], a great result given the limited information available and the duration of time to follow-up and similar to that traced by Nash et al (1983) [44].…”
Section: Methodsmentioning
confidence: 93%
“…The Tall Girls Study traced 87% of women identified as eligible from medical records [1], a great result given the limited information available and the duration of time to follow-up and similar to that traced by Nash et al (1983) [44]. The effectiveness of different strategies will vary greatly between countries; it is important to tailor strategies according to local circumstances to obtain optimal results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with Nash et d . , 8 local tracing activities prove to be the most productive, and depend on a dedicated and persistent field team. We were fortunate to recruit one field supervisor whose previous employment had provided substantial experience in these techniques, and who provided teams at other sites with practical consultation which augmented the methods cited in the m a n~a l .~~,~~ However, as Nash et al note,8 tracing beyond the local area increases expenses due to travel time and costs, suggesting the use of agencies with existing capacity to perform this task.…”
Section: Discussionmentioning
confidence: 99%